2015
DOI: 10.14483/udistrital.jour.calj.2015.1.a02
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ attitudes, perceptions and experiences in CLIL: A look at content and language

Abstract: This paper is a preliminary report on the "CLIL State of the Art" project in Colombia, drawing on data collected from 140 teachers' regarding their attitudes toward, perceptions of, and experiences with CLIL (content and language integrated learning). The term CLIL is used here to refer to teaching contexts in which a foreign language (in these cases, English) is the medium for the teaching and learning of non-language subjects. The data that has been gathered thus far reveal that while teachers presently know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 5 publications
5
55
0
3
Order By: Relevance
“…Moreover, they believed that CLIL helps students develop both language skills and subject knowledge. Consistent with the findings reported by McDougald (2015), the participants responded that CLIL developed language skills and subject knowledge. Nonetheless, it was found that the majority of the participants noted that time was necessary for lesson planning and teaching.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, they believed that CLIL helps students develop both language skills and subject knowledge. Consistent with the findings reported by McDougald (2015), the participants responded that CLIL developed language skills and subject knowledge. Nonetheless, it was found that the majority of the participants noted that time was necessary for lesson planning and teaching.…”
Section: Discussionsupporting
confidence: 87%
“…Even more disconcerting is that the policy predominantly configures itself around a linguistic fashion: the erroneous idea that language principally consists of grammar memorization and metalinguistic knowledge. As of yet, there is little evidence on how this policy would go beyond this basic conception of language learning to include current trans-disciplinary approaches that entail content-based methodologies in the English classroom such as CLIL (a phenomenon which has timidly emerged in the Bogotá region in the past few years [McDougald, 2015]), an intercultural dimension, and even a pragmatic competence. Having said this, this paper argues that CB and precedent policies are evidently including English in the curriculum to attain a mechanical level of the language.…”
Section: Unanswered Questionsmentioning
confidence: 99%
“…The program is at a stage of on-going implementation in which students currently in third grade have increased the number of subjects instructed in English since 2014 to date (2016) when they finally have 50% of their curriculum in English. This study focused on the evaluation of CLIL in science as it is the only content subject that is assessed by the national standard tests, has a relevant number of hours in the curriculum, and is the second most popular content subject taught in Colombian Bilingual Schools (McDougald, 2015).…”
Section: Context Of the Studymentioning
confidence: 99%
“…This national tendency has led private and public schools to the implementation of programs without regard to learners' needs analysis, context characteristics, and required resources (Lugo-Vásquez, Fandiño-Parra, & Bermúdez-Jiménez, 2012). Additionally, little research has been conducted in Colombia regarding the actual effects of CLIL: one study was found at the university level (Otálora, 2009), one at elementary school level (Mariño, 2014), two regarding teachers' perceptions and experiences (Curtis, 2012a) (Curtis, 2012b) (McDougald, 2015 and two more related to the state of CLIL in Colombia (McDougald, 2009), (Rodríguez, 2011.…”
Section: Introductionmentioning
confidence: 99%